The role of 4-pba on tnf-alpha related apoptosis on human vein endothelial cells - Illiandri, Oski (Bangladesh Journal of Medical Science, 2019)
Tumor Necrotizing Factor-alpha (TNF-α) has been well-known as a potent pro-inflamatory cytokine involved in many degenerative disease. Oneof its primary target organ-damaged wasendothelial cellswhich willlead to its endoplasmic reticulum stress (ERS) and induced its apoptosis. Endothelial cell apoptosis will lead high implication in many disease pathomechanism ofmany degenerative disease. Some study report ERS inhibitor 4-Phenyl Butyric Acid (4-PBA) properties to inhibitinflammation processin endothelial cells.However, wether 4-PBA can decrease apoptosis level in inflamationof endothelial cells is still poorly understood Objective. This study to answer whether 4-PBA can decrease apoptosis triggered by inflammatory reactions mediated by TNFα. Methods: This study is an exploratory study laboratory in vitro using cell culture Human Umbilical Vein Endothelial Cells (HUVEC) apoptotic count cells with the design of post test only control group consisting of three treatment groups with doses of 4-PBA 1 nM / mL, 2 nM /mL, and 3 nM /m L. Results. Administration4-PBA in cultured HUVEC derived endothelial cells significantly decrease apoptosis at any dose of PBA but no dose dependently (p <0.05) Conclusion: Based on the results that has been done, it can be concluded that 4-PBA can reduce levels of endothelial cells apoptosis which were exposed to proinflamatory cytokine TNF-α. Further research need to elucidated 4-PBA mechanism to inhibit endothelial apoptosis. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.391-394